1989
DOI: 10.1063/1.102149
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen surface coverage: Raising the silicon epitaxial growth temperature

Abstract: The role of hydride coverage in surfacelimited thinfilm growth of epitaxial silicon and germanium Equilibrium surface hydrogen coverage during silicon epitaxy using SiH4Electronic surface changes induced in silicon by hydrogen, oxygen, and cesium coverages

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

1990
1990
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(12 citation statements)
references
References 7 publications
0
12
0
Order By: Relevance
“…Several models, including defect accumulation, 25 continuous breakdown, 17,25 hydrogen-induced breakdown, [25][26][27][28][29][30] and kinetic roughening 4,6 -8,11-13,24,25 have been suggested to explain the observed epitaxial-to-amorphous transition. Defect accumulation and continuous breakdown models involve, in their simplest form, a continuous temperature-dependent increase in the concentration of lattice disorder.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several models, including defect accumulation, 25 continuous breakdown, 17,25 hydrogen-induced breakdown, [25][26][27][28][29][30] and kinetic roughening 4,6 -8,11-13,24,25 have been suggested to explain the observed epitaxial-to-amorphous transition. Defect accumulation and continuous breakdown models involve, in their simplest form, a continuous temperature-dependent increase in the concentration of lattice disorder.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been pro-posed that adsorbed hydrogen from the residual background gas leads to epitaxial breakdown as H terminates dangling bonds, thereby altering the surface reconstruction template and hindering adatom migration. [25][26][27][28][29][30] Intentional H 2 dosing at Ӎ2ϫ10 Ϫ2 ML s Ϫ1 ( P H 2 ϭ2ϫ10 Ϫ6 Torr͒ during MBE Si͑001͒ growth at T s ϭ310 and 200°C with Rϭ1.0 Å s Ϫ1 decreased the epitaxial thickness from Ӎ1000 to 200 Å and from Ӎ300 to 20 Å, respectively. [25][26][27][28] Finally, there is evidence indicating that kinetic surface roughening itself plays an important role in controlling epitaxial breakdown.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Recently, we have demonstrated that Si growth by remote plasma enhanced chemical vapor deposition ͑RPCVD͒ exhibits three distinct growth modes. 3 This work suggested that the onset of three-and twodimensional epitaxial growth is governed by di-and monohydride desorption, respectively.…”
mentioning
confidence: 99%
“…Since hydrogen is the most abundant residual gas in any stainless steel chamber, it has been suspected to be responsible for the breakdown of Si epitaxy at low temperatures from the beginning. Wolff et al first showed that molecular hydrogen, even with very low sticking coefficient on Si surfaces, can adversely affect the crystal structure of the grown Si film for growth temperatures below the H desorption temperature about 783 K. 2 They attributed the breakdown of epitaxy to a critical hydrogen coverage at the growth front which is attained by hydrogen segregation.…”
Section: Introductionmentioning
confidence: 99%